Development of STEM-based discovery learning student worksheets with Lastek game to improve physics learning outcomes of grade XI students at SMA Negeri 2 Singkep - Andriani, Riza; Irawan , Dody; Zaitun , Zaitun; Kumalasari , Tety; Nevrita , Nevrita (Educenter : Jurnal Ilmiah Pendidikan, 2025)
This research was motivated by the low conceptual understanding and learning outcomes of eleventh-grade students at SMA Negeri Dua Singkep, caused by teacher-centered learning and the use of conventional teaching materials. This study aimed to develop a Discovery Learning-based Student Worksheet integrated with the STEM approach and the Lastek game as an innovative learning medium, and to test its feasibility, practicality, and effectiveness in Physics learning. The research method used was Research and Development with the ADDIE model, encompassing the stages of analysis, design, development, implementation, and evaluation. The subjects were eleventh-grade students of SMA Negeri Dua Singkep in the academic year of 2024 to 2025. The results showed that the developed Student Worksheet had a very high level of validity, was easy to use in the learning process, and was effective in improving conceptual understanding and student learning outcomes. Therefore, the STEM-based Discovery Learning Student Worksheet with the Lastek game is deemed suitable for use as a teaching material to support interactive, contextual, and student-centered Physics learning.